THE EFFECT OF INTEGRATED LOGISTICS SUPPORT SYSTEM ON LIFE CYCLE MANAGEMENT - Sulhi Eski; İlker Hakan Özaslan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The Life Cycle is defined as a process that begins with the demonstration of an intended ability and ends when it becomes out of use. Extending the life cycle will reduce costs and increase efficiency.Integrated Logistics Support (ILS); It increases the service life of the products and minimizes the need for support; In this way, it provides financial benefit by reaching higher gains in the long term. Due to the understanding of these benefits, it is a system that is frequently applied by businesses. By successfully applying ILS, the life cycle of aircraft, systems, tools and equipment is extended and costs are reduced.The aim of the study; A product or a system integrated to provide maximum use of the opportunity at minimal cost by extending the life cycle of the Logistics Support Turkey is to identify and remedy the causes of failure of the application.Fieldwork method and interview technique were used in the study. The reasons for the failure of the Integrated Logistics Support application on the life cycle have been identified through a study on aircraft. It has been determined;The positive effect of Integrated Logistics Support especially extends the life cycle, prevents premature modification, prevents price increases in spare parts supply, facilitates the availability of spare parts, facilitates the provision of technical documentation, provides planning and execution of personnel training, and the problems of supplying special tools with the system or vehicle.